Comparative analysis of RPL14 expression between tumour cell lines colorectal system - Selvamalar, Mutsamy (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Cancer progresses by the accumulation of genetic alterations that consequently leads to gene expression pattern changes. Colorectal carcinoma (CRC) is one of the most common cancer that is being studied as it offers an excellent opportunity to study molecular events. There is growing evidence that ribosomal protein (RP) may have extraribosomal functions despite their essential role in protein biosynthesis. To date, numerous research have reported that this group of genes are also associated with various human disorders and malignancies. Previous studies have revealed that ribosomal protein gene L14 (RPL14) are underexpressed in lung, oral and oesophagus carcinoma. However, there is no published data concerning the relationship between RPL14 and human colorectal carcinoma. Therefore, our study aimed to evaluate the gene expression patterns of RPL14 in CRC. We examined the expression level of RPL14 in colorectal carcinoma cell lines, namely HCTl16 and SW480 via reverse transcription-PCR approach. Student's t-test were used to determine the statistical significance of the results obtained. Our findings revealed that there is a significant expression level ofRPL14 in HCTl16 cell line relative to SW480 cell line atp<O.OS.